Government bond market risk-return trade-off - Christiansen, Charlotte; Savva, Christos S. (My University, 2023)
We analyze the risk-return trade-off for international (France, Germany, Netherlands, Spain, UK, and US) government bond markets and the US stock market. We measure risk by the higher order moments (volatility, skewness, and excess kurtosis) as they are defined in Savva and Theodossiou (2018). There is no risk-return trade-off when considering a linear relationship between returns and risk. We consider good and bad volatility separately as defined by threshold regressions and find non-linear risk-return trade-off, that is negative for large lagged returns.
Keywords: bad volatility; good volatility; government bond markets; risk-return trade-off